PENULISAN CERPEN BERBASIS KEARIFAN LOKAL SUMATERA SELATAN DENGAN METODE IMAGE STREAMING DALAM PROSES KREATIF MAHASISWA - Dian Nuzulia Armariena; Liza Murniviyanti (Universitas PGRI Palembang, 2017)
This research is intended to improve students' ability in writing short stories. Writing literature at the University level should be applied to produce short stories of high aesthetic value. However, students have difficulty in putting their thoughts into writing. What's more, they encounter obstacles in developing creative ideas that are written down in literary writing. Therefore, the researcher targets that the idea of stories based on local wisdom of South Sumatra will facilitate students in the creative process of developing the story.Creative process is supported by the method of learning that is image streaming method in achieving the learning objectives of improving the ability to write a student in short story and the result of a collection of short stories based on local wisdom of South Sumatra. The long-term goal is to create independent, creative, and productive student characters in an effort to empower themselves to explore local wisdom of South Sumatera by writing short stories. This study was designed for one year through class action research procedures (PTK). The subject of this research is the students of semester VI c who follow the course of “Menulis Karya Sastra” at FKIP of PGRI University of Palembang in academic year 2016/2017 which consist of 27 students. To measure the level of success in mastering the ability to write short stories, students are given the task to write short stories at the end of the action learning activities as an evaluation.Based on the result which has been done at the stage of cycle I and cycle II students of class VIc University PGRI Palembang in writing, showed that the image streaming method can improve students' writing skills in short story. It is showed by the improvement of each stage starting from the first cycle phase which is 29.6% to 63% in cycle II.